DIFFERENCES IN SIDE EFFECTS BETWEEN USERS OF 1-MONTH INJECTABLE CONTRACEPTION AND 3-MONTH INJECTABLE CONTRACEPTION IN BOALEMO REGENCY - Delia Windiyani Eka Putri Daka; Irwan Irwan; Zul Fikar Ahmad (Gorontalo State University, 2023)
Kontrasepsi suntik adalah cara untuk mencegah terjadinya kehamilan dengan melalui suntikan hormonal. Kebaruan penelitian ini karena menganalisis perbedaan efek samping pada pengguna KB suntik 1 bulan dan KB suntik 3 bulan. Tujuan penenlitian ini untuk menganalisis perbedaaan efek samping pada pengguna KB suntik 1 bulan dengan 3 bulan di Desa Tenilo Kecamatan Paguyaman Kabupaten Boalemo. Metode penelitian adalah obeservasi analitik dengan pendekatan studi Cross Sectional. Populasi penelitian ini adalah seluruh Ibu akseptor KB suntik di Desa Tenilo yang seluruhnya dijadikan sampel dengan jumlah 104 orang yang terdiri dari 52 responden pengguna KB suntik 1 bulan dan 52 responden pengguna KB suntik 3 bulan yang ditentukan dengan teknik pengambilan sampel Total Sampling. Analisis data bivariat menggunakan uji Mann-whitney. Hasil penelitian didaptkan nilai p-value 0,000 0,05 yang artinya terdapat perbedaan efek samping pada pengguna KB suntik 1 bulan dengan KB suntik 3 bulan. Kesimpulan penelitian ini terdapat perbedaan efek samping pada pengguna KB suntik 1 bulan dengan KB suntik 3 bulan di Desa Tenilo Kecamatan Paguyaman Kabupaten Boalemo.Kata Kunci: Efek samping; KB suntik 1 bulan; KB suntik 3 bulan.AbstractInjectable contraceptives are a way to prevent the occurrence of pregnancy using hormonal injections. The novelty of this study is due to analyzing the differences in side effects in users of 1-month injectable birth control and 3-month injectable birth control. The purpose of this research is to analyze the difference in side effects in users of injectable birth control for 1 month with 3 months in Tenilo Village, Paguyaman District, Boalemo Regency. The research method is analytical observation with a Cross-Sectional study approach. The population of this study was all injectable kb acceptor mothers in Tenilo Village, all sampled with a total of 104 people consisting of 52 respondents who used 1-month injectable birth control and 52 respondents who used 3-month injectable birth control determined by the Total Sampling technique. Bivariate data analysis using the Mann-Whitney test. The study results obtained a p-value of 0.000 0.05, meaning there are differences in side effects in users of 1-month injectable birth control with 3-month injectable KB. This study concluded that there were differences in side effects in users of 1-month injectable birth control with 3-month injectable birth control in Tenilo Village, Paguyaman District, Boalemo Regency.